Identification of the SRC-family tyrosine kinase HCK as a therapeutic target in mantle cell lymphoma - Lantermans, Hildo C.; Minderman, Marthe; Kuil, Annemieke; Kersten, Marie-José; Pals, Steven T.; Spaargaren, Marcel (Leukemia, 2021)
Mantle cell lymphoma (MCL) is an aggressive non-Hodgkin lymphoma subtype arising from naïve B cells. Although novel therapeutics have improved patient prognosis, drug resistance remains a key problem. Here, we show that the SRC-family tyrosine kinase hematopoietic cell kinase (HCK), which is primarily expressed in the hematopoietic lineage but not in mature B cells, is aberrantly expressed in MCL, and that high expression of HCK is associated with inferior prognosis of MCL patients. HCK expression is controlled by the toll-like receptor (TLR) adaptor protein MYD88 and can be enhanced by TLR agonists in MCL cell lines and primary MCL. In line with this, primary MCL with high HCK expression are enriched for a TLR-signaling pathway gene set. Silencing of HCK expression results in cell cycle arrest and apoptosis. Furthermore, HCK controls integrin-mediated adhesion of MCL cells to extracellular matrix and stromal cells. Taken together, our data indicate that TLR/MYD88-controlled aberrant expression of HCK plays a critical role in MCL proliferation and survival as well as in retention of the malignant cells in the growth- and survival-supporting lymphoid organ microenvironment, thereby contributing to lymphomagenesis. These novel insights provide a strong rationale for therapeutic targeting of HCK in MCL.